ITRAQ-based proteomic analysis reveals key proteins affecting cardiac function in broilers that died of sudden death syndrome. (11th September 2019) - Ning, Hongmei; Cui, Yunli; Song, Xiaochao; Chen, Lingli; Yin, Zhihong; Hua, Liushuai; Ren, Fei; Suo, Yu; Wang, Xinrui; Zhang, Hongli; Hu, Dongfang; Ge, Yaming
ABSTRACT: Sudden death syndrome (SDS ), which is a cardiac-related condition commonly observed in chickens selected for rapid growth, causes significant economic losses to the global poultry industry. Its pathogenesis in broilers is poorly understood, and little is known about the proteome of the heart tissue of SDS broilers. A quantitative proteomic approach using isobaric tags for relative and absolute quantification labeling of peptides was used to characterize the protein expression profiles in the left ventricle of SDS broilers. These proteins were further analyzed by bioinformatics, and two proteins were validated by western blot analysis. We identified 186 differentially expressed proteins (DEPs ), of which 72 were upregulated, and 114 were downregulated in the SDS group. Functional annotation suggested that 7 DEPs were related to cardiac muscle contraction, and another 7 DEPs were related to cardiac energy metabolism. Protein interaction network predictions indicated that differences in cardiac muscle contraction between SDS and healthy groups were regulated by troponin T, tropomyosin alpha-1 chain, fast myosin heavy chain HCIII, myosin-1B, coronin, and myoglobin, whereas differences in cardiac energy metabolism and biosynthesis of amino acids were regulated by gamma-enolase, phosphoglycerate mutase, NADH-ubiquinone oxidoreductase chain 2, serine/threonine-protein kinase, myoglobin, and alpha-amylase. Our expression profiles provide useful information and new insights into key proteins to elucidate SDS for further studies.